Sistem Pakar Menggunakan Forward Chaining Untuk Memprediksi Gangguan Kejiwaan - Vany Terisia; Akmal Annafis; Arman, Shevti Arbekti (Jurnal Teknologi Informasi (JUTECH), 2024)
Mental health is one of the most important aspects of human life, especially in the modern era, which is filled with stress and challenges. However, many individuals are reluctant or face difficulties in accessing mental health services due to social stigma and limited resources. To address this challenge, this study developed a web-based expert system to predict an individual's mental health condition using the Forward Chaining method. The Forward Chaining method is utilized to analyze symptoms inputted by users based on predefined rules, enabling the system to provide accurate initial diagnoses and appropriate recommendations. The application is designed to be user-friendly and easily accessible, assisting individuals in obtaining mental health information and support without fear of stigma. Additionally, the system also has the potential to serve as a supporting tool for mental health professionals in providing efficient initial diagnoses.